Relationship between Leader Communication Skills and Team Performance in Pakistan - Ali, Asif (American Journal of Leadership and Governance, 2024)
Purpose: The aim of the study was to assess the relationship between leader communication skills and team performance in Pakistan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that leaders who communicate effectively are able to articulate clear goals, provide constructive feedback, and foster an environment of open dialogue, all of which significantly enhance team performance. Effective communication by leaders helps in aligning team members with organizational objectives, improving coordination, and facilitating problem-solving. Moreover, it enhances trust and morale among team members, leading to increased engagement and commitment. Studies also indicate that leaders with strong communication skills are better at conflict resolution and can adapt their communication style to suit different team dynamics, further contributing to higher team productivity and cohesion. Overall, the ability of leaders to convey their vision and expectations clearly and empathetically is crucial in driving the success of their teams. Implications to Theory, Practice and Policy: Transformational leadership theory, social identity theory and transactional leadership theory may be used to anchor future studies on assessing the relationship between leader communication skills and team performance in Pakistan. Organizations can enhance their practices by investing in communication skills training for leaders. Developing and implementing communication guidelines or policies can have a significant impact on organizational communication practices. These guidelines outline expectations, best practices, and channels for effective communication, ensuring consistency and clarity across the organization.